Faculty Versus Resident Self-Assessment Using Pathology Milestones: How Aligned Are We?. (13th December 2021) - Athy, Sienna; Talmon, Geoffrey; Samson, Kaeli; Martin, Kimberly; Nelson, Kari
Competent physicians must be able to self-assess skill level; however, previous studies suggest that medical trainees may not accurately self-assess. We utilized Pathology Milestones (PM) data to determine whether there were discrepancies in self- versus Clinical Competency Committee (CCC) ratings by sex, program year (PGY), time of evaluation, and question category (Patient Care, Medical Knowledge, Systems-Based Practice [SBP], Practice-Based Learning and Improvement [PBL], Professionalism [PRO], and Interpersonal and Communication Skills) and Residency In-Service Examination (RISE) score. We completed retrospective analyses of PM evaluation scores from 2016 to 2019 (n = 23 residents) 2 times per year. Discrepancies in evaluation scores were calculated by subtracting CCC scores from resident self-evaluation scores. There was no significant difference in discrepancy scores between male versus female residents (P = .94). Discrepancy scores among all PGYs were significantly different (P < .0001), with PGY1 tending to overrate the most, followed by PGY2. PGY3 and PGY4 underrated themselves on average compared to CCC ratings, with PGY4 having significantly lower self-ratings than CCC compared to any other PGY. In January, residents underscored themselves and in July residents overscored themselves compared to CCC (P < .0001 for both). Question types resulted in variable discrepancy scores, with SBP significantly lower than and PRO significantly higher than all other categories (P < .05 for both). Increases in RISE score correlated to increases in self- and CCC-scoring. These discrepancies can help trainees improve self-assessment. Discrepancies indicate potential areas for amelioration, such as curriculum adjustments or Milestone's verbiage.